In Pursuit of a Good Conversation: How Contribution Balance, Common Ground, and Conversational Closings Influence Conversation Assessment and Conversational Memory. Issue 1 (2nd January 2023) - Guydish, Andrew J.; Fox Tree, Jean E.
ABSTRACT: How do people determine whether a conversation is good or bad? Do conversational phenomena (reaching common ground, striving to contribute equally, successful conversational closings) influence judgments of conversation quality and recall of conversations? We tested whether individuals reading previously transcribed conversations considered psycholinguistic characteristics in their assessments of whether the conversations were good or bad. Additionally, we tested whether these assessments influenced how the conversations were remembered. Well-formed interactions (balanced, grounded, or with well-structured closings) were rated as better than ill-formed counterparts (not balanced, not well grounded, or with poorly structured closings). When recalling the best interaction they saw, participants chose a well-formed conversation about 80% of the time. When recalling the worst interaction they saw, they chose an ill-formed conversation about 90% of the time. Balance information was important to both judgments. Participants recognized well-balanced conversations more accurately and were also faster to recognize well-balanced conversations. In contrast, participants recognized ill-formed grounding better, although it took more time to do so. Well-formed and ill-formed closings were recognized to a similar degree, but improperly structured closings were recognized more quickly. These findings support the hypothesis that common ground, contribution balance, and conversational closings influence both perception of conversational quality and memory for previously transcribed conversations.